1987
DOI: 10.1002/ijc.2910400621
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced metastases of a mouse carcinoma after in vitro treatment with murine interferon gamma

Abstract: We have studied the influence of interferons (IFNs) on the metastatic potential of mouse colon adenocarcinoma, COLON 26, cells. Pre-treatment of the cells in vitro for 24 hr with recombinant murine IFN-gamma (rMuIFN-gamma) significantly increased the number of lung tumour nodules when cells were injected i.v. into immunocompetent BALB/c mice and BALB/c nude mice. However, when MuIFN-gamma-pre-treated cells were injected into beige (NK-deficient) nude mice or anti-asialoGM 1 (asGM 1)-serum-treated BALB/c mice (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
20
1

Year Published

1987
1987
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 17 publications
5
20
1
Order By: Relevance
“…Consistent results were obtained in repeated experiments on LAK cells generated from patients with RCC, as well as those from [32]. On the other hand, it has also been reported that IFN-induced protection is observed without any increase in class I molecules [15,21]. Correlation between susceptibility to LAK cells and class I antigen expression on target cells is still controversial.…”
Section: Discussionsupporting
confidence: 70%
“…Consistent results were obtained in repeated experiments on LAK cells generated from patients with RCC, as well as those from [32]. On the other hand, it has also been reported that IFN-induced protection is observed without any increase in class I molecules [15,21]. Correlation between susceptibility to LAK cells and class I antigen expression on target cells is still controversial.…”
Section: Discussionsupporting
confidence: 70%
“…Although IFN-␥ should contribute to tumor-suppressive actions of IL-18 in vivo, antitumor functions of IL-18 have been observed in an IFN-␥-independent manner (31,32,34). It is noteworthy that under defined conditions, IFN-␥ in fact appears to be capable of enhancing growth of colon carcinomas (36). Induction of IL-18BP by IFN-␥ might contribute to this observation.…”
Section: Discussionmentioning
confidence: 94%
“…IFN-γ inhibits metastasis of mouse ovarian and lung tumour cells (Ossina et al, 1997), renal adenocarcinoma cells (Yanagihara et al, 1994) and human non-small-cell lung cancer cells (Masumori et al, 1995). By contrast, it enhances experimental metastatic potential of colon 26 adenocarcinoma cells and B16 melanoma cells (Ramani and Balkwill, 1987). These results may be due to the time of treatment of the cells with IFN-γ, as suggested by some investigators (McMillan et al, 1987), or the properties of each cell line.…”
Section: Discussionmentioning
confidence: 96%